NILAI-NILAI SUFISME DALAM KITAB AL-HIKAM DAN RELEVANSINYA DENGAN PENGEMBANGAN PENDIDIKAN SOFTSKILL - Rohmat Saichu AL Haromaini; Yogi Prana Izza (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
This study aims to determine the Sufistic values contained in the Kitab al-hikam by Ibn Atha'illah as-Sakandari and its relevance to the development of soft skills education. This research is important because soft skills play an important role in determining life success. The approach used in this study is qualitative with library research methods. The primary data is Kitab al-hikam. Through content analysis, we will dissect the Sufistic values taught by Shaykh Athoilah in his book. Furthermore, these values are examined for suitability to the development of soft skills education. From this research, it was found that the Sufistic values in Kitab al-Hikam are the values of tawakal, istiqamah, sincerity, gratitude and patience, repentance and honesty. These six values are very volunteer to be developed in soft skills education